Latent Transition Analysis indicates four relatively stable profiles of loneliness in New Zealand - Matthew D. Hammond; Laura E. Goulden; Chris G. Sibley; Taciano L. Milfont (Elsevier, 2022)
Abstract Objective: We investigated the characteristics of loneliness by identifying distinct 'profiles' of loneliness and investigating transitions between those loneliness profiles over two years. Method: We conducted Latent Transition Analyses on two years of data from the New Zealand Attitudes and Values Study (N=15,820) and modelled how people's health and age were associated with changes in profile membership. Results: Four loneliness profiles emerged: 'low‐loneliness' (58% of the sample), 'high‐loneliness' (5%), 'appreciated outsiders' (28%; perceived acceptance from others but felt like social outsiders), and 'superficially connected' (9%; lacked acceptance from others but felt socially included). Profile membership was relatively stable over time and transitions were most likely from higher to lower loneliness. Younger people and people reporting poorer health were more likely to transition into profiles with greater loneliness indicators. Conclusions: Findings replicated a four‐profile pattern of loneliness, supported the theorised 'trait‐like' structure of loneliness and identified the possibility that moderate states of loneliness are transitional states into/from low and high loneliness. Implications for public health: The stability of loneliness across years reiterates the need for societal interventions, particularly interventions that are adaptive to whether people's loneliness forms as a lack of acceptance/value or a lack of social inclusion.